Electric vehicle integration’s impacts on power quality in distribution network and associated mitigation measures: a review - Srivastava, Abhinav; Manas, Munish; Dubey, Rajesh Kumar (Journal of engineering and applied science (Online), 2023)
The problem of global warming, along with environmental concerns, has already led governments to replace fossil-fuel vehicles with low-emission electric vehicles (EVs). The energy crisis and environmental problems, such as global warming and air pollution, are essential reasons for the development of electric vehicles (EVs). Electric vehicles are one of the most fascinating and essential fields to emerge in recent years. According to the current report, electric vehicles are attempting to replace older, traditional automobiles. These vehicles not only help to reduce pollution but also to save natural resources. The presence of electric vehicles may cause several problems for the conventional electrical grid due to their grid-to-vehicle (G2V) and vehicle-to-grid (V2G) charging and discharging capabilities. With increased EV adoption, many power quality (PQ) issues in the electrical distribution system arise. With the penetration of EVs in distribution networks, power quality issues such as voltage imbalance, transformer failure, and harmonic distortion are expected to arise. The focus of this research is on exploring and reviewing the issues that the integration of EVs poses for electrical networks. The existing and future situations of electric vehicles’ integration, as well as new research on the subjects, have been reviewed in this paper. This study provides a thorough examination of power quality issues and their mitigating approaches.